Single-step generation of metal-plasma polymer multicore@shell nanoparticles from the gas phase - Solař, Pavel; Polonskyi, Oleksandr; Olbricht, Ansgar; Hinz, Alexander; Shelemin, Artem; Kylián, Ondřej; Choukourov, Andrei; Faupel, Franz; Biederman, Hynek (Scientific reports, 2017)
Nanoparticles composed of multiple silver cores and a plasma polymer shell (multicore@shell) were prepared in a single step with a gas aggregation cluster source operating with Ar/hexamethyldisiloxane mixtures and optionally oxygen. The size distribution of the metal inclusions as well as the chemical composition and the thickness of the shells were found to be controlled by the composition of the working gas mixture. Shell matrices ranging from organosilicon plasma polymer to nearly stoichiometric SiO2 were obtained. The method allows facile fabrication of multicore@shell nanoparticles with tailored functional properties, as demonstrated here with the optical response.